PERSEPSI PEMUSTAKA TERHADAP PEMINJAMAN KOLEKSI SECARA MANDIRI DI PERPUSTAKAAN UNIVERSITAS ANDALAS - Dwiki Adyolga; Ardoni Ardoni (CV. ADIBA AISHA AMIRA, 2023)
This study aims to determine the user's perception of borrowing collections independently at the Andalas University Library. The factors that influence a person's perception are as follows: Stereotypes, self-perception, situations and groups, characteristics that exist in other people. The service quality of a library can be evaluated from five dimensions as follows: Ease of use, Reliability, Efficiency, Convenience, Security. The method used in this research is descriptive method. The population of this research is the active students of Andalas University, totaling 32,326. Sampling uses the Slovin formula, so that the number of samples is 100 people. The sampling technique used Simple random sampling technique. The data collection used Google from which included 9 indicators, namely about user perceptions and borrowing collections independently. So the results showed that most users answered that they were happy about borrowing collections independently at the Andalas University library.